Requirements for flushing of different mixtures of growing media for tomato grown under controlled environment greenhouse - Abd. Jamil Z. (Malaysian Society of Soil Science, 2022)
Tomatoes var. 'Baccarat' were grown in plastic bed under rainshelter and insect proof netted structure controlled environment (CE). Different proportions of medium size perlite at 0% (T1), 10% (T2), 20% (T3) 30% (T4) and 40% (T5) were added to the initially mixed media containing locally obtained coco peat and paddy husk charcoal in the ratio of 7:3. At 2 months after planting, media flushing treatments were given at intervals of 2 weeks (T1), 4 weeks (T2) and 6 weeks (T3). Initially no effect of flushing were detected but after about 5 months from planting significantly higher media EC were found when the media were flushed at every 6 weeks intervals as compared to 2 or 4 weeks interval. These higher EC caused reduction in the fruit yield, fruit number and average fruit size at the later period (inflorescence number 11 to 18). Coco peat initially mixed with 30 % paddy husk charcoal resulted in lower EC when added with 40% perlite. This low EC resulted in significant higher fruit yield, fruit number and average fruit weight of the tomato plant.